2003
DOI: 10.1007/bf02492121
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties and chromatographic behavior of a mixture of two liquid crystals

Abstract: Key WardsGas-liquid chromatography Liquid crystal mixtures as stationary phases Differential scanning calorimetry Aromatic hydrocarbons and phenols SummaryThe thermal and chromatographic properties of an equimolecular mixtu re of I',,vo liquid crystals have been investigated. Differential scanning calorimetry showed that the clearing temperature of the mixture is intermediate bel',,veen the corresponding temperatures for the individual liquid crystals. The melting temperature was lower than the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Thermotropic liquid crystal have drawn the attention of the chromatographers to be as stationary phases in gas chromatography follows from their unique separating properties, which are due to the structure and ordering of their molecules [1] . At a certain temperature range (from the melting point to the point of transition to the isotropic liquid phase) thermotropic liquid crystal have some degree of orientation molecular ordering, and thus have properties that are intermediate between the solid and the isotropic liquid [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Thermotropic liquid crystal have drawn the attention of the chromatographers to be as stationary phases in gas chromatography follows from their unique separating properties, which are due to the structure and ordering of their molecules [1] . At a certain temperature range (from the melting point to the point of transition to the isotropic liquid phase) thermotropic liquid crystal have some degree of orientation molecular ordering, and thus have properties that are intermediate between the solid and the isotropic liquid [2] .…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with previous studies in which increased solubility of p-cresol was observed. This is typical of nematic phases [21,22]. Dimethylphenol derivatives were better eluted with the LCUT column, in the order 2,6-, 2,4-, 2,3-, 3,5-, and 3,4-dimethylphenol.…”
Section: Efficiency and Durability Of Lcspsmentioning
confidence: 99%
“…These unique solvent properties of liquid crystals were reported for the first time by Kelker [7] and by Dewar and Schroeder [8,9] and were initially applied to the separation of the positional isomers of various disubstituted benzenes. Since this pioneering work, a large number of publications describe the analytical performance of liquid crystals [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and several reviews outlining the fundamentals and applications of liquid crystal stationary phases (LCSPs) in both packed and capillary columns are available [27][28][29][30][31][32][33][34][35][36]. Up to now, the results of the studies on LCSPs indicate that the chromatographic behavior of liquid crystals is basically dependent on its molecular structure in which a slight change in the molecular geometry brings about considerable change in its thermal and analytical properties.…”
Section: Introductionmentioning
confidence: 99%